Study guides

☆☆

Q: -2b plus 7-3b equals 2

Write your answer...

Submit

Related questions

If: a = 2b+c Then: a-c = 2b And: b = (a-c)/2

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

Whan a = 2 and b = 6, 5a + 2b = 5*2 + 2*6 = 10 + 12 = 22

3a + 2b = (3*6) + (2*5) = 18 + 10 = 283a+2b= (3x6)+(2x5)= 18+10=28

A = 2b + cSubtract 'c' from each side:A - c = 2bDivide each side by 2:b = 1/2 (A - c)

4b^2

2a + 2b = c subtract 2a from both sides 2a - 2a + 2b = c - 2a 2b = c - 2a divide both sides by 2 (2/2)b = (c - 2a)/2 b = (c - 2a)/2 --------------------

3 times 6 is 18 2 times 5 is 10 18 plus 10 is 28

2b-6=20 2b=26 b=26/2 b=13

a = 2b - c a + c = 2b (a+c)/2 = b b = (a+c)/2

2(a+b) is 2a plus 2b in factored form.

b= 1/2 (a - c)

If this was b exponent 2 (squared) or b^2 for the first b, then it is a quadratic expression. b^2 + 2b - 11 = 88 b^2 + 2b - 99 = 0 (b+11)(b-9) = 0 B = -11 or 9

If 2b a plus c, then we can say that 3tan A 2tan c = 21.

5b - 3 - 2b = 6b - 3 3b - 3 = 6b - 3 3b - 6b = 3 - 3 b = 0

I ask my 11 year old son. 2b + 18 = 4b Subtract 2b form each side: 18 = 2b Divide each side by 2: 9 = b which is the same as b = 9, but you knew that, didn't you?

3a + 2b = 4If b = 7, then3a + 2(7) = 43a + 14 = 4Subtract 14 from each side:3a = -10Divide each side by 3:a = -10/3

(a2 + 2)(b + 3)

Yes, the answer is the square root of 2b.

2a + 2b = 26 2b + c = 22 ===> b = 11 - c/2 4c + 2b = 46 ===> b = 23 - 2c From the 2nd and 3rd equations: 11 - c/2 = 23 - 2c 22 - c = 46 - 4c 22 - 46 = -4c + c ===> -24 = -3c ===> c = 8 Substitute c=8 into the 3rd equation: b = 23 - 16 = 7 Substitute b=7 into the 1st equation: 2a + 14 = 26 2a = 12 ===> a = 6

Technically, a-2b=2 is the actual answer. Since you wouldn't have to put it in y=mx+b form, the equation can no longer be simplified.

= a + b - 2

It is: b+4 when simplified

You use Plus as a symbol in Maths. Example, 2 Plus 2 equals 4. Or in symbols it would be 2+2=4. __________________________ Plus = + Equals = = (Equals equals =)

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).